The oxygen reduction reaction on graphitic carbon nitride supported single Ce atom and CexPt6-x cluster catalysts from first-principles. (April 2018) - He, Feng; Li, Huiqi; Ding, Yingchun; Li, Kai; Wang, Ying; Wu, Zhijian
Abstract: The single atom or cluster catalysts supported by two dimensional (2D) materials are the most promising low cost alternatives to the pure Pt catalyst for the oxygen reduction reaction (ORR). In this work, we have investigated the ORR mechanism on the g-C3 N4 supported single Ce atom (i.e., Ce/g-C3 N4 ) and cluster (i.e., Cex Pt6-x /g-C3 N4 ) theoretically. Our study shows that Ce atom can be tightly bound to the g-C3 N4 substrate and the presence of Ce atom is extremely favorable for the anchoring of Cex Pt6-x clusters on the substrate. The Ce/g-C3 N4 shows similar ORR catalytic activity compared with bulk Pt. The reaction is a four-electron process. The most favorable pathway is the hydrogenation of OOH to form O + H2 O. On the other hand, Cex Pt6-x /g-C3 N4 (x = 0, 1, 3, 5, 6) is thermodynamically stable and shows a very different catalytic behavior. Particularly, the working potential is predicted to be 0.50 V for Ce3 Pt3 /g-C3 N4, implying that it is a potential ORR catalyst. Graphical abstract: Image 1